(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
In contemporary formative relationships there is an attitudinal and epistemic need to make the city a space for the aesthetic experience to exist and, therefore, one of the ways in which such an educational premise, which slips directly into the formation of new spectators, can be consolidated as an area of knowledge and field of experience, it would be the regular occupation of public spaces by different aesthetic actions, thus, Universities are not outside of this context. Thus, in an essayistic way, the following work raises some reflections on the training potential that the city can offer in the construction of aesthetic artifacts and, also, some possible relationships between curriculum, city and culture in artistic training.